Analysis of Organizational Culture and Appreciation of Organizational Commitment with Work Motivation as a Mediating Variable at the Medan Belawan Tax Office Medan Belawan Primary Tax Office - Imam Ananda; Hernawaty Hernawaty; Mesra B (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
Organizational commitment is an important factor in improving the performance and sustainability of public organizations, especially in tax agencies that have high service demands and state revenue targets. This study aims to analyze the influence of organizational culture and rewards on organizational commitment with work motivation as a mediating variable at the Medan Belawan Tax Office. This study uses a quantitative approach with a census method on all 100 permanent employees. Primary data were collected through questionnaires and analyzed using Partial Least Squares (PLS) with the help of the SmartPLS application. The results showed that organizational culture had a positive and significant effect on work motivation and organizational commitment. Rewards were also found to have a positive and significant effect on work motivation and organizational commitment. In addition, work motivation had a positive and significant effect on organizational commitment. The indirect effect test shows that work motivation can significantly mediate the relationship between organizational culture and rewards on organizational commitment. The coefficient of determination shows that organizational culture and rewards can explain 41.8% of the variation in work motivation, while organizational culture, rewards, and work motivation together explain 49.3% of organizational commitment. Based on these results, it can be concluded that strengthening organizational culture and a fair and sustainable reward system, accompanied by increased work motivation, are important strategies in improving employee organizational commitment in the Medan Belawan Tax Office environment. This study is expected to provide practical contributions to tax agency management in human resource management as well as theoretical contributions to the development of public management studies.